2016
DOI: 10.12968/ijtr.2016.23.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Engaging patients with moderate to severe acquired brain injury in goal setting

Abstract: Background/Aims: An exploratory study of a novel approach to using the Goal Engagement Scale to examine patients', families' and health professionals' perceptions of patient engagement in goal setting. Methods: This mixed methods study was conducted from September 2013 to April 2014 in both inpatient trauma and rehabilitation units at an Australian health care service. Participants were 22 triads (patients with moderate to severe traumatic brain injury or stroke, their family member(s) and a treating health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Other qualitative studies have used direct observation of practice to examine the application of goal setting in clinical settings (D'Cruz et al, 2016;Levack et al, 2011). For example, Levack et al examined interdisciplinary team goal setting with nine inpatients with stroke and found that the goal setting process privileged goals of higher clinical priority, which meant at times providing client-centred care was difficult (Levack et al).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other qualitative studies have used direct observation of practice to examine the application of goal setting in clinical settings (D'Cruz et al, 2016;Levack et al, 2011). For example, Levack et al examined interdisciplinary team goal setting with nine inpatients with stroke and found that the goal setting process privileged goals of higher clinical priority, which meant at times providing client-centred care was difficult (Levack et al).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Levack et al . examined interdisciplinary team goal setting with nine inpatients with stroke and found that the goal setting process privileged goals of higher clinical priority, which meant at times providing client‐centred care was difficult (Levack et al .). In an observational study of practice with 22 inpatients with ABI, D'Cruz et al . found that in order to engage clients in goal setting, practitioners explored the experience of injury and hospitalisation, built trusting relationships through reflective listening, responded to individual needs and used a collaborative process to elicit goals. However, in some cases despite setting client‐centred goals, discharge priorities were the focus of intervention (D'Cruz et al .).…”
Section: Introductionmentioning
confidence: 99%
“…Although not unique to TLS programmes, studies in our review found that goal setting be collaborative, with trust developed between all parties. Consistent with the broader research on engagement in goal-setting after brain injury, the TLS studies also found that the process of goal setting enables successful active engagement in rehabilitation for both residents and families (Guertson, 2008;D'Cruz et al, 2016;Duchnick et al, 2015;McColl et al, 1999). Therefore, there is a need for TLS programmes to support residents and families to be actively engaged in goal setting.…”
Section: Discussionmentioning
confidence: 63%
“…Research which provides insight into how to set goals is needed as this study did not measure the effect that other cognitive impairments had on participation in goal setting. Given that self-awareness impairment has been identified as a factor which may influence client perception of their level of engagement in goal setting (D'Cruz et al, 2016), further research is required to better understand how impaired self-awareness impacts on the development of client-centred goals.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%